2011
DOI: 10.4103/0970-1591.91433
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic reconstruction of iatrogenic-induced lower ureteric strictures: Does timing of repair influence the outcome?

Abstract: Context:Influence of timing of repair on outcome following laparoscopic reconstruction of lower ureteric stricturesAims:To assess the influence of timing of repair on outcome following laparoscopic reconstruction of lower ureteric strictures in our adult patient population.Settings and Design:Single surgeon operative experience in two institutes. Retrospective analysis.Materials and Methods:All patients were worked up in detail. All patients underwent cystoscopy and retrograde pyelography prior to laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
2
4
0
Order By: Relevance
“…Recently, several reported studies on robotic ureteroneocystostomy have been published showing successful results similar to those obtained with the laparoscopic technique. [ 20 22 23 24 25 26 27 28 29 ] The present study results are in similar lines with the previous conducted studies as depicted in Table 3 . Uberoi et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Recently, several reported studies on robotic ureteroneocystostomy have been published showing successful results similar to those obtained with the laparoscopic technique. [ 20 22 23 24 25 26 27 28 29 ] The present study results are in similar lines with the previous conducted studies as depicted in Table 3 . Uberoi et al .…”
Section: Discussionsupporting
confidence: 92%
“…Abraham et al . [ 20 ] concluded that in hemodynamically stable patients, laparoscopic repair of iatrogenically induced lower ureteric strictures can be conveniently undertaken without undue delay from the inciting event. Compared to delayed repairs, the procedure is technically more demanding but morbidity incurred and outcome is at par.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature also suggests the similar findings and concluded that laparoscopic ureteroneocystostomy is a safe and feasible option for lower ureteric stricture (Tables 3 and 4). [8][9][10][11][12][13][14][15][16][17][18][19] limitation of this study are, it is a single centre nonrandomised study with a small sample size.…”
Section: Resultsmentioning
confidence: 99%
“…22 Since then many studies had been published favouring the role of laparoscopy in ureteroneocystostomy. [9][10][11][12][13][14][15][16][17][18][19] Ureteroneocystostomy with or without Psoas hitch and Boari flap can be done using laparoscopic approach with a good success rate and having all advantage of minimal access surgery. 11 We were able to complete 93% of our laparoscopic surgery without need of conversion to open procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation